Mineral solubilizing microorganisms and their combination with plants enhance slope stability by regulating soil aggregate structure - Wang, Lingjian; Tang, Xinggang; Liu, Xin; Xue, Rengui; Zhang, Jinchi (Frontiers in Plant Science, 2023)
The stability of exposed slopes is prone to natural disasters, seriously threatening socioeconomic and human security. Through years of exploration and research, we proposed an active permanent greening (APG) method based on patented mineral solubilizing microorganisms (MSMs) as an improvement over the traditional greening method. In this study, we selected two MSMs (Bacillus thuringiensis and Gongronella butleri) and a plant species (Lolium perenne L.) set up six treatments (T1, T2, T3, T4, T5, and T6, specific information shown in Table 1) to investigate the effectiveness of the MSMs and their combinations with the plant species on the soil stability using APG method. We noted that both MSMs and the plant species significantly improved soil aggregate stability and organic matter content. Of all the treatments, the T1 treatment exhibited better results, with soil aggregate stability and organic matter content increased to 45.63 % and 137.57 %, respectively, compared to the control. Soil stability was significant positively correlated with macroaggregate content and negatively with microaggregates. Using structural equation modeling analysis, we further evaluated the mechanism underpinning the influence of organic matter content and fractions on the content of each graded agglomerates. The analysis showed that the macroaggregate content was influenced by the presence of the plant species, primarily realized by altering the content of organic matter and aromatic and amide compounds in the agglomerates, whereas the microaggregate content was influenced by the addition of MSMs, primarily realized by the content of organic matter and polysaccharide compounds. Overall, we observed that the effect of the co-action of MSMs and the plant species was significantly better than that of using MSMs or the plant species alone. The findings of this study provide reliable data and theoretical support for the development and practical application of the APG method to gradually develop and improve the new greening approach.